Resistansi Tokoh Utama terhadap Konflik dalam Film Ḥilm Al-Zaytūn Perspektif Teori Georg Simmel - Ukhrawiyah, Faizetul; Kurniawati, Fauziyah (Faculty of Humanities, Diponegoro University, 2025)
This research aims to elaborate on the main character's resistance to conflict in the movie Ḥilm al-Zaytūn from the perspective of Georg Simmel's theory and to express the impact of that resistance on the circulation of conflict in movies. The data in this research were collected by watching a movie as the main material for data collection, listening to dialogue, character expressions, storylines, and note-taking elements related to the research objectives. The data were analyzed using data reduction, display, and conclusion drawing techniques. The results show that the main character's resistance to various conflicts according to Georg Simmel contained in movie Ḥilm al-Zaytūn is calmness, nobility, firmness of attitude, and courage. According to Georg Simmel, the forms of conflict found in movies are intimate relationship, antagonistic, and importance conflicts. The impact of resistance toward intimate relationship conflict is a compromise between the individuals involved in the conflict. The impact of resistance toward antagonistic conflict is the recognition of the end of conflict by outsiders. The impact of resistance toward important conflict is the elimination of conflict bases and victory over the acceptance of defeat by outsiders. The social interaction between groups or individuals will become stronger through the resistance of groups or individuals toward conflict.